Some Aspects of Postoperative Management of Patients with Ovarian Cancer after Cytoreductive Surgery Using Hyperthermic Intraperitoneal Chemotherapy (HIPEC) - D. D. Morikov; V. I. Gorbachev; A. G. Pavlov; V. V. Dvornichenko; A. V. Shelekhov; N. D. Morikov; S. I. Radostev (Вестник анестезиологии и реаниматологии, 2022)
The objective. Analysis of the course of the postoperative period and number of complications in patients with ovarian cancer during cytoreductive operations with hyperthermic intraoperative intra-abdominal chemotherapy.Subjects and Methods. We assessed the number of bed-days, the volume of infusion-transfusion therapy, diuresis, the volume of enteral feeding, the level of leukocytes, urea, creatinine, and lipocalin associated with gel in 45 patients with ovarian cancer after cytoreductive surgery with hyperthermic intraoperative intra-abdominal chemotherapy.Results. All patients developed polyuria while reference parameters of urea and creatinine were stable. Due to these changes, additional markers of acute renal damage were searched for. 15.9% of cases developed leukopenia on days 7–10. The number of complications and deaths does not exceed the world level.Conclusion. A multicomponent and versatile approach to the postoperative management of patients allows minimizing the level of complications and deaths. A search for a more sensitive marker of acute kidney injury is needed.